Coagulation factor XII regulates inflammatory responses in human lungs - Hess, Rosanna; Wujak, Lukasz; Hesse, Christina; Sewald, Katherina; Jonigk, Danny; Warnecke, Gregor; Fieguth, Hans-Gerd; Maat, Steven de; Maas, Coen; Bonella, Francesco; Preissner, Klaus T.; Weiss, Benjamin; Schaefer, Liliana; Kuebler, Wolfgang M.; Markart, Philipp; Wygrecka, Malgorzata (Thrombosis and Haemostasis, 2017)
Increased procoagulant activity in the alveolar compartment and uncontrolled inflammation are hallmarks of the acute respiratory distress syndrome (ARDS). Here, we investigated whether the contact phase system of coagulation is activated and may regulate inflammatory responses in human lungs. Components of the contact phase system were characterized in bronchoalveolar lavage fluids (BALF) from 54 ARDS patients and 43 controls, and their impact on cytokine/chemokine expression in human precision cut lung slices (PCLS) was assessed by a PCR array. Activation of the contact system, associated with high levels of coagulation factor XIIa (Hageman factor, FXIIa), plasma kallikrein and bradykinin, occurred rapidly in ARDS lungs after the onset of the disease and virtually normalized within one week from time of diagnosis. FXII levels in BALF were higher in ARDS nonsurvivors than survivors and were positively correlated with tumor necrosis factor (TNF)-α concentration. FXII induced the production and release of interleukin (IL)-8, IL-1β, IL-6, leukemia inhibitory factor (LIF), CXCL5 and TNF-α in human PCLS in a kallikrein-kinin-independent manner. In conclusion, accumulation of FXII in ARDS lungs may contribute to the release of pro-inflammatory mediators and is associated with clinical outcome. FXII inhibition may thus offer a novel and promising therapeutic approach to antagonize overwhelming inflammatory responses in ARDS lungs without interfering with vital haemostasis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Acute respiratory distress syndrome; contact phase system; coagulation factor XII